2014
DOI: 10.1007/s13679-014-0097-8
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Prevention in Latin America

Abstract: In Latin American countries, obesity prevalence has increased significantly as a result of rapid urbanization and an improvement in socioeconomic conditions. We report the prevalence of overweight and/or obesity and prevention efforts in five countries: Mexico, Colombia, Brazil, Peru, and Chile. In children, the highest and lowest rates of obesity are found in Chile (23 % in 6-year-olds) and Peru (1.8 % in those <5 years), respectively. In adults, Mexico and Chile present similar high rates of obesity (around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 18 publications
0
27
0
2
Order By: Relevance
“…Thus, currently the prevalence of overweight in children from Latin America is over 25 %,whereas in adults, it is higher than 50 %.The prevalence of obesity in children also reached more than 3 % (exception in Peru where for preschool children it is less than 2 %), and in adults, this prevalence is higher than 25 % [18]. In Brazilian children, overweight prevalence ranged from 25 to 40 % and among adolescents, it is 22 % in boys and 19.4 % in girls [18]. Recently, a meta-analysis conducted in Brazil showed that the overall prevalence of obesity among children/adolescents was 14.1 %.…”
Section: Obesity Prevalence and Risks In Children And Adolescentsmentioning
confidence: 99%
“…Thus, currently the prevalence of overweight in children from Latin America is over 25 %,whereas in adults, it is higher than 50 %.The prevalence of obesity in children also reached more than 3 % (exception in Peru where for preschool children it is less than 2 %), and in adults, this prevalence is higher than 25 % [18]. In Brazilian children, overweight prevalence ranged from 25 to 40 % and among adolescents, it is 22 % in boys and 19.4 % in girls [18]. Recently, a meta-analysis conducted in Brazil showed that the overall prevalence of obesity among children/adolescents was 14.1 %.…”
Section: Obesity Prevalence and Risks In Children And Adolescentsmentioning
confidence: 99%
“…LA's aging population has grown, pushing up rates of NCDs risk factors and the prevalence of NCDs in the region. Obesity and physical inactivity are now especially important public health challenges (Barreto et al, 2012, Frenk et al, 1991, Kain et al, 2014, Rivera et al, 2002). …”
Section: Introductionmentioning
confidence: 99%
“…Mexico and Chile are now amongst the nations with the highest overweight and obesity rates in the world-- over 70% in both countries. 3,4 Brazil has the 4 th highest prevalence of diabetes in the world: nearly 12 million people (or roughly 10% of the Brazilian population) have diabetes. 1,5,6 The costs associated with this growing epidemic are substantial.…”
Section: Introductionmentioning
confidence: 99%
“…4 While the rate of economic development has been uneven across the region, in general economies in LACs have improved, with a reduction in poverty and increased urbanization. 4 Although these trends have brought many benefits, they also have been accompanied by changes in physical activity levels and diet that have contributed to the increase in diabetes.…”
Section: Introductionmentioning
confidence: 99%